Faktor Pendukung Perkembangan Usaha Konveksi: Studi pada Abu Bakar Konveksi Metro - Rahayu, Siti Nurpuji; Sainul, Sainul; Nuriasari, Selvia; Suci, Okta Adioni Tinokae Rahma (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
The clothing industry is very promising and the conditions for profit are in line with the rise of clothing trends or fashions in society. Departing from this, today there are small and medium businesses that produce clothes (convection) causing a great deal of market competition. This has resulted in many convection businesses not being able to develop or even experiencing setbacks. But behind the high market competition, there are still many convection businesses that are still able to maintain their existence or even develop, one of which is the Abu Bakar Convection business. Departing from this, the purpose of conducting this research is to find out the factors that influence the development of the Abu Bakar Convection business. According to Hendro, there are 8 factors that can affect business development, namely opportunity factors, human resources, finance and administration, organization, planning, business management, marketing and sales, and government assistance.This study uses a qualitative descriptive analysis method with data collection techniques through interviews and documentation. Based on the research results, there are 6 factors that influence the development of the Abu Bakar Convection business, namely opportunity factors, human resources, organization, planning, business management, and marketing and sales.The results of this study can be used as a basis for making policies for business owners of Abu Bakar Convection to improve their business development and can also be used as learning for prospective entrepreneurs, especially in the convection sector.